2013
DOI: 10.1177/0148607113505860
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition in Various Political, Economic, and Geographic Settings

Abstract: The prevalence of malnutrition was quite high in some countries, and the nutrition approach differed among them. It could be the result of the lack of reimbursement, inactive or nonexistent NSTs, and low nutrition awareness. Those facts confirmed that the continuation of FAM activities is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…Undernutrition, defined as a state of altered body composition and body cell mass resulting from a lack of uptake or intake of nutrition that leads to diminished physical and mental function and impaired outcomes from disease [1], affects up to 65% of hospitalized patients [2,3]. Malnutrition can make a person more susceptible to infection, and infection also contributes to malnutrition, which leads to a vicious cycle [2].…”
Section: Introductionmentioning
confidence: 99%
“…Undernutrition, defined as a state of altered body composition and body cell mass resulting from a lack of uptake or intake of nutrition that leads to diminished physical and mental function and impaired outcomes from disease [1], affects up to 65% of hospitalized patients [2,3]. Malnutrition can make a person more susceptible to infection, and infection also contributes to malnutrition, which leads to a vicious cycle [2].…”
Section: Introductionmentioning
confidence: 99%
“…In general, up to 30% of hospitalized patients received some type of specialized NS [8]. Usually, a high frequency of hyperglycemia is observed in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the prevalence of malnutrition varies from almost 10 to 60% depending on the hospital and country [1][2][3] . In hospitals worldwide, it is found that malnutrition greatly influences diseases and disease recovery and therefore is a major challenge in the Key Words NutritionDay · Malnutrition · Nutrition support · Length of hospital stay Abstract Background and Aims: Malnutrition is a common and critical problem that greatly influences the clinical outcomes of hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%